MEMODELKAN TINGKAT PENGANGGURAN TERBUKA DI INDONESIA - MAHENDRA, KADEK YUSA; SUSILAWATI, MADE; SUCIPTAWATI, NI LUH PUTU (E-Jurnal Matematika; Vol 10 No 1 (2021), 2021)
Unemployment is one of the problems in the field in economic development. To determine the development of open unemployment in a region, an indicator of the open unemployment rate is used. The highest of open unemployment rate is Aceh Province and Maluku Province in 2015 at 9,93 percent and the lowest Bali Province in 2018 at 1,37 percent. The purpose of this work is to modeling and determine the significant factors that affect the open unemployment rate in Indonesia by applying spatial panel data regression. The results show indicate that there is no effect of spatial dependence on the model, so the model chosen to model the open unemployment rate in Indonesia is a panel data model with a fixed time effect and significant affect by head count index, the percentage of illiterate people, the provincial minimum wage, and the number of the workforce.